Longitudinal extensive transverse myelitis following ChAdOx1 nCOV-19 vaccine: a case report - Tan, Wee Yong; Yusof Khan, Abdul Hanif Khan; Mohd Yaakob, Mohd Naim; Abdul Rashid, Anna Misyail; Loh, Wei Chao; Baharin, Janudin; Ibrahim, Azliza; Ismail, Mohd Redzuan; Inche Mat, Liyana Najwa; Wan Sulaiman, Wan Aliaa; Basri, Hamidon; Hoo, Fan Kee (BioMed Central, 2021)
Background: Transverse myelitis (TM) is a relatively uncommon condition, and vaccine-associated myelitis is even rarer. Concern regarding neurological complications following vaccination escalated following the report of TM during the safety and efcacy trials of the COVID-19 vaccine. Case presentation: We report the frst case of Longitudinal Extensive Transverse Myelitis (LETM) in Malaysia following administration of the chimpanzee adenovirus-vectored (ChAdOx1 nCoV-19) vaccine. A 25-year-old female presented with bilateral lower limb weakness and inability to walk with a sensory level up to T8 with absent visual symptoms. Urgent gadolinium-enhanced magnetic resonance imaging (MRI) of the spine showed long segment TM over the thoracic region. Cerebrospinal fuid autoantibodies for anti-aquaporin-4 and anti-myelin-oligodendrocyte were negative. A diagnosis of LETM following vaccination was made, and the patient was started on a high dose of intravenous methylprednisolone. The patient eventually made a recovery following treatment. Conclusion: LETM is a rare but serious adverse reaction following vaccination. Previously reported cases showed an onset of symptoms between 10 to 14days post-vaccination, suggesting a delayed immunogenic reaction. However, the incidence of myelitis in COVID-19 is much more common, far greater than the risk associated with vaccination.